The impact of export instability on Malaysia's economic growth - Abu Bakar, Nor'Aznin; Subramaniam, Shri Dewi (2010)
This study examines the relationship between export stability and economic growth in Malaysia using time series analysis techniques that address the problem of nonstationarity.The Augmented Dickey Fuller (ADF) and residual based tests are used to test for stationarity of all variables and cointegration, respectively. Findings from this study show that in Malaysia's case, all variables involved are non-stationary in levels but stationary in first dzferences and are cointegrated. The export instability has a deleterious efect on Malaysia's economic growth. Instability in export earnings can cause economic reprisals, which will afect the economic performance of the country. The balance of payment positions will be jeopardized, unemployment levels would increase and individuals' income levels may decrease.